Differential sensitivity of human papillomavirus type 16+ and type 18+ cervical carcinoma cells to CD95-mediated apoptosis - Carmen Aguilar Lemarroy, Adriana del; Zur Hausen, Harald; Krammer, Peter H.; Rösl, Frank (International journal of cancer, 2001)
When cervical carcinoma cells were monitored for apoptotic signals, HPV18+ lines were found to be highly sensitive to agonistic CD95 antibodies or recombinant CD95 ligands after co-exposure with CHX (CD95S). In contrast, HPV16+ cervical carcinoma cells and HPV16-immortalized non-malignant human keratinocytes were CD95-resistant (CD95R) under equivalent conditions. Somatic cell hybridization between CD95S and CD95R cervical carcinoma cell lines revealed that CD95 sensitivity was a dominant trait, which could be correlated with abundant c-Myc and low Bcl-XL expression. Although CD95R cervical carcinoma cells expressed even higher levels of p53 and CD95 receptor at the surface, resistance could be attributed to the inability to form a functional DISC, necessary for successful transmission of the apoptogenic response. These data indicate that resistance to apoptotic stimuli represents an important immunological escape mechanism during virus-induced carcinogenesis.
Gesehen am 27.04.2021
Im Titel sind die Pluszeichen hochgestellt